Ukuran Dewan Komisaris, Komisaris Independen, Debt to Equity Ratio: Pembuktian pada BUMN Holding di Indonesia - Simbolon, Ramadona (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2024)
This study aims to empirically test the role of Board of Commissioners Size and Independent Commissioners on Debt to Equity Ratio (DER) in companies incorporated in the BUMN Holding structure in Indonesia. The study population includes all BUMN company entities that have undergone restructuring through the formation of a holding, with an observation period of one year after the holding was officially formed. The purposive sampling method was used in selecting the sample, resulting in 50 BUMN companies that met the criteria as objects of analysis. The findings of this study show interesting results that only Independent Commissioners are proven to have a positive and significant effect on DER, while the Size of the Board of Commissioners does not have a significant effect. This shows that the quality and independence of supervision are more important than the quantity of board members in influencing the company's capital structure decisions. Based on these findings, the government as the majority shareholder needs to be more selective in appointing members of the board of commissioners, by considering professional capabilities and maintaining their independence and objectivity in making strategic company decisions. In addition, this study recommends that the government strengthen the role and proportion of Independent Commissioners in the BUMN Holding governance structure. This effort is not only important in improving the accountability and effectiveness of internal supervision, but also contributes to increasing the credibility of state-owned companies in the eyes of investors, creditors, and financial market players more broadly